2012
DOI: 10.1039/c2cp42595e
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric stability of lipid bilayers

Abstract: In agreement with recent reports, a commercial densimeter has yielded a gradual decrease in lipid molecular volume of DPPC multilamellar vesicle dispersions in the gel phase upon repeated thermal cycling between 10ºC and 50ºC. The considerable size of this decrease would have significant implications for the physical chemistry of biomembranes. In contrast, neutral buoyancy measurements performed with similar thermal cycling indicate no gradual change in lipid volume in the gel phase at 20ºC. Remixing the lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Between each heating and cooling scan the sample was removed and replaced in the densimeter, since we previously determined that lipid settling over time can cause an artifactual increase in density in the DMA densimeter. 54 The change of slope at 24 °C was quite reproducible. According to multiple phase diagrams of monoolein in water, there is no lipid phase transition near 24 °C at high hydration, such as in our sample.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Between each heating and cooling scan the sample was removed and replaced in the densimeter, since we previously determined that lipid settling over time can cause an artifactual increase in density in the DMA densimeter. 54 The change of slope at 24 °C was quite reproducible. According to multiple phase diagrams of monoolein in water, there is no lipid phase transition near 24 °C at high hydration, such as in our sample.…”
Section: Resultsmentioning
confidence: 86%
“…Care was taken not to cause foam on the top of the sample from the sonication. This sample preparation differed from the usual protocol of temperature cycling between 60 °C and −20 °C with vortexing, 54 since vortexing and cold temperature caused the lipid to clump. Samples with a monoolein concentration > 1 wt % also clumped more easily.…”
Section: Methodsmentioning
confidence: 97%
“…The physical state of the membrane, and hence K W , in the gel phase are affected by the presence of PA and LPPC, due perhaps to lateral phase separation, and induced defects [23, 24]. The DPPC bilayer expands by about 5 % upon transition from gel to liquid [25, 26]. At 50 °C, it is in the more relaxed liquid phase to begin with.…”
Section: Discussionmentioning
confidence: 99%
“…of temperature is 0.01 and 0.03 C, respectively (Instruction Manual to DMA 4500 M). The total measurement time of one sample was maximally 1.5 h. Hallinen et al (2012) and Murugova and Balgavý (2014) reported an artificial change in density of multilamellar PC liposomes after a long-term storage of sample in the U-tube of a vibrating density meter. This effect is related to a time dependent sedimentation of multilamellar liposomes.…”
Section: Methodsmentioning
confidence: 98%